Development and Validation of Inductively Coupled Plasma Mass Spectrometry Method for Quantification of Lithium in Whole Blood from Forensic Postmortem Cases - Cherrie Cheuk Yiu Chang; Sys Stybe Johansen; Brian Schou Rasmussen; Kristian Linnet; Ragnar Thomsen (Forensic Sciences)
Lithium is used as a medication in the treatment of bipolar disorder. Lithium has a narrow therapeutic index, and fatal intoxications have been described. The therapeutic drug monitoring of lithium is routinely performed in serum. Serum is commonly unavailable in forensic postmortem analysis, where whole blood is the matrix of choice. In this study, an inductively coupled plasma mass spectrometry (ICP-MS) method was developed and validated for the quantification of lithium in postmortem whole blood. Sample preparation consisted of a 100-fold dilution with acid and required only 40 µL of blood. Carry-over was deemed appropriately reduced with a rinse solution containing 5% hydrochloric acid. A nebulizer gas flow rate of 1.15 L/min showed a sufficient improvement of lithium sensitivity while simultaneously minimizing the background. Germanium was determined to be the most optimal internal standard. The method was validated in terms of linearity, accuracy, precision, and lower limit of quantification. Linearity was demonstrated within the analytical measurement range of 0.10–1.5 mmol/L. The method showed acceptable precision and accuracy, with a total coefficient of a variation ≤2.3% and accuracies ranging from 105 to 108% at all concentrations in the quality control samples. The final method was applied to postmortem blood from 103 consecutive autopsy cases and demonstrated robustness by low intermediate precision and high and consistent recovery of the internal standard.